The lake of darkness - Rendell, Ruth frey50 (Doubleday & Co., Inc. Garden, City, NY, 1980)
The life of a strait-laced London accountant is drastically altered by his winning a hugh sum of money in the football pools and by the people this new-found wealth brings into his life.